A qualitative study: the influence of occupational therapy for pelvic floor dysfunction on functioning, disability, and health - Pearce, Delaney M., author; Schmid, Arlene A., advisor; Atler, Karen E., committee member; Fruhauf, Christine A., committee member (Colorado State University. Libraries, 2022)
Introduction: Approximately one quarter of all women in the United States experience symptoms of pelvic floor dysfunction (PFD). Occupational therapy (OT) for PFD is a relatively new area of expertise within the field, resulting in limited research on its efficacy. Objectives: Explore the ways in which OT for PFD influences health using the International Classification of Functioning, Disability, and Health (ICF) as a guide. Method: Four participants completed the study. Eligibility criteria included: >18 years old, biologically female, English speaking, self-reported pelvic floor issue, completed OT intervention for PFD within the last two years. Electronic medical records and Pelvic Floor Distress Inventory Questionnaire-10 (PFDI-20) scores prior to and after completing OT intervention for PFD were reviewed, and semi-structured interviews were conducted. Results: Four themes emerged: 1) improved mental health and physiological function, 2) promotion of the mind-body connection, 3) reintroduction of meaning, and 4) relationships with healthcare professionals and sociocultural influences. Each theme is tied to a component of the ICF. Conclusion: OT for PFD has a positive impact on health per the ICF. This may result in better function and participation in everyday life. More research is needed to investigate the generalizability of these findings.
Keywords: ICF; occupational; therapy; incontinence; dysfunction; pelvic floor